Dimensions underlying academic procrastination among university students: An exploratory factor analysis and intervention implications - Merina Pratiwi; Amiroel Oemara Syarief (Institute of Computer Science (IOCS), 2026)
Academic procrastination is a persistent problem among university students and negatively affects academic performance and timely study completion. This phenomenon is closely related to students’ ability to manage time, regulate academic behavior, and respond to environmental and technological demands. However, empirical evidence on the underlying factor structure of academic procrastination in local higher education contexts remains limited. This study aims to identify the latent factor structure of academic procrastination using Exploratory Factor Analysis (EFA). A quantitative design was employed by administering a 20-item academic procrastination questionnaire to undergraduate students. Data were analyzed using Principal Axis Factoring with Promax rotation. Data suitability was confirmed by a Kaiser–Meyer–Olkin value of 0.902 and a significant Bartlett’s Test of Sphericity. The EFA results revealed two dominant factors: time management and academic self-regulation, and environmental and technology-related distractions. These findings provide empirical evidence on the dominant dimensions of academic procrastination and support the development of targeted institutional interventions in higher education.